f(x)=tan(2x)cot(2x)

Simple and best practice solution for f(x)=tan(2x)cot(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=tan(2x)cot(2x) equation:


Simplifying
f(x) = tan(2x) * cot(2x)
Multiply f * x
fx = tan(2x) * cot(2x)
Remove parenthesis around (2x)
fx = ant * 2x * cot(2x)
Remove parenthesis around (2x)
fx = ant * 2x * cot * 2x
Reorder the terms for easier multiplication:
fx = 2 * 2ant * x * cot * x
Multiply 2 * 2
fx = 4ant * x * cot * x
Multiply ant * x
fx = 4antx * cot * x
Multiply antx * cot
fx = 4acnot2x * x
Multiply acnot2x * x
fx = 4acnot2x2
Solving
fx = 4acnot2x2
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Divide each side by 'x'.
f = 4acnot2x
Simplifying
f = 4acnot2x

You can always share this solution

See similar equations:

| 2w^2+7w+2=0 | | -16.1x^2+4x+10=0 | | 71/8-23/4= | | 8ab(6ab-2)= | | 5+s=17 | | 8a^2+6a+5= | | 6+10x=-48+x | | altX+1=4 | | x+2(2x-3)=12 | | r(z^2-13)+(z^2-13)=0 | | 8y=1+7x | | x+(-x-2)=2x-4 | | 3x+5.2=25x | | .7d=4.2 | | -13=5 | | -77-3x=-9x+43 | | 0.3x-0.7y=0 | | 7b^2-14b-5b=0 | | 7r^3-14r^2+7r=0 | | 3*x^3-9*x^2-9*x+9= | | z(y+5)-7(y+5)=0 | | 782-10-13=m | | m+10+13=782 | | 11x^2-3y^2-88x+18y+116=0 | | 6w-2(4+W)=1w+7 | | x^2-33-2x=0 | | 6X-10X=-9+8 | | 4(4x-2.2)=4x-8.8 | | -68x+71=-65 | | 6x+5z=6+5y | | (5x-3)-(x+5)=2x+4 | | 0=2x^2-16x-8 | | x^2-4x+9=25-4x | | rad(x+12)-rad(x-15)=3 | | f(x)=tan^3(3x) | | 4x+12y=-76 | | 11x-65=5x+109 | | B(b-4)=96 | | g(x)=xsquared+6x+4 | | 2y=2px | | m+8=13+m | | 22x+87=72x+93 | | 3(3Y-3)-2(2Y-2)=10 | | (n-8)3=100 | | -8(t+7)+3(7t+6)=12(t-3)+3 | | 7(cos^2)x-2sinx+2=0 | | 2-0.4= | | -48+2m+m^2=0 | | -38+10x=4x+58 | | (S-9)9= | | f(x)=cos(2x)sin(2x) | | -3(t+6)=6 | | 2x-3=7x+8 | | 18+4y-2=17y-11-4y | | 2(2r-3)= | | 4(x-6)+4=-4x-4 | | 2x^2=7+6x | | 6=3p | | -4(q-4)= | | 6+6=3n | | -31+22=-8x+11x | | (x-17)+(x+25)=180 | | 130+4x+2=180 | | 5U-8=92 | | (p-3)(-8)= |


Related pages


table of prime factorshow to graph 2x 5y 10prime factorization for 57ln3 ln2prime factorization 35prime factorization of 34greatest common factor of 120what is the prime factorization for 54192 168 2121log2 642.2kg in lbmultiples of 252what is the prime factorization of 186x2 5x 3 03.5.0find all solutions of the equation calculatorprime factorization of 112square root of 150 simplified10x squaredprime factorization for 64how to solve prime factorizationsolve v lwh for lx 2 2x factorsquare root of 2704find the prime factorization of 96solve x2 4x 8 0factoring x 3 x 2 x 197 prime factorization9x 2 4y 2 36simplify tanx cotxfive eighths as a percentagewhat is the lcm of 6factors of49prime factorization of 210prime factorization 84prime factorization 35what is lnx times lnx2sibsin2x cos 2xderivative of 1 cosx1800-130012000 rupees to dollars3x-5y 13 x-2y 54x 2y 8 0loga log b5v to 9v5y0simplify 3x 6xeighty four is what percent of 212polynomial factoring calculator with stepsdividing fractions calculatorsqrt 196derivative of sine cubedprime factorization of 135cos pi 12 step equation calculator with fractions3x 5y 25sin 3x sin x273.15 k to c13.125 as a fractionsin2xdxsolve for equation calculatorcollege measuredsuccess comcommon multiples of 7 and 34fggreatest common factor of 48 and 64how to graph y 4xof612y kx2gcf of 10815x 1 12y 2x 4derivative of x ln x